MORPHODYNAMIC OF BARITO DELTA, SOUTHERN KALIMANTAN - , Deasy Arisanty; , Prof. Dr. Junun Sartohadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The morphodynamic of Barito Delta has positive and negative influence to the peoples who live in the delta and surrounding areas. The continues sedimentation may rejuvenate soils to perform fertile soil, in the other hand it also can suppress the transportation activities. The objectives of research are: (1) to evaluate the short term morphodynamic in Barito Delta, and (2) to evaluate the long term morphodynamic in Barito Delta. First objective has three sub objectives, i.e.: to analyze the characteristic river discharge